School Management and Student Achievement: The Case of One Private School - Ridho, M.; Yahya; Hadiyanto; Rifma (Universitas Jambi, Indonesia, 2024)
This qualitative research aimed to look at how the principal’s management could improve student achievement in one private school. The research informants were the principal, deputy principal, teachers, and students. The researchers used observation, interviews, and document studies. The data analysis techniques consist of data collection, display, reduction, and conclusion. The results showed that the principal used SWOT analysis, setting goals, and establishing programs, arranged an organizational structure and divided tasks based on their respective responsibilities, provided a direction and guidance, adequate facilities and infrastructure. Also, the principal participated in competitions according to the school budget, encourages educators and motivation, used direct and indirect evaluation. Additionally, the principal had professional teachers. Meanwhile, the inhibiting factors were inadequate educational support facilities.